2008
DOI: 10.1128/mcb.00943-07
|View full text |Cite
|
Sign up to set email alerts
|

GATA-1 Modulates the Chromatin Structure and Activity of the Chicken α-Globin 3′ Enhancer

Abstract: Long-distance regulatory elements and local chromatin structure are critical for proper regulation of gene expression. Here we characterize the chromatin conformation of the chicken ␣-globin silencer-enhancer elements located 3 of the domain. We found a characteristic and erythrocyte-specific structure between the previously defined silencer and the enhancer, defined by two nuclease hypersensitive sites, which appear when the enhancer is active during erythroid differentiation. Fine mapping of these sites demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…7a). Chicken red blood cells (RBC) CTCF ChIP experiments were performed as previously described 44,45 . We evaluated the CTCF-ChIP quality with several positive and negative PCR controls (Supplementary Figure 7b).…”
Section: Methodsmentioning
confidence: 99%
“…7a). Chicken red blood cells (RBC) CTCF ChIP experiments were performed as previously described 44,45 . We evaluated the CTCF-ChIP quality with several positive and negative PCR controls (Supplementary Figure 7b).…”
Section: Methodsmentioning
confidence: 99%
“…2Bii) networks. Judged by the number of connections, GATA-1 appears to be an influential TF with respect to both hemin- and PMA-mediated differentiation and is known to recruit many proteins to mediate chromatin remodeling (Escamilla-Del-Arenal and Recillas-Targa, 2008; Grass et al, 2003; Im et al, 2005). According to the model, GATA-1 is a target of most TFs that were screened.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the histone H3K4me2 modification and the polyacetylation of histone H3 and H4 are drastically enriched in SW480 cells (Figure 1c). To corroborate the in situ chromatin status of the promoter we performed a restriction enzyme accessibility assay (Escamilla-Del-Arenal and Recillas-Targa, 2008) (Figure 1d). The results of these experiments are in accordance with the previous assays, and they show that the p53 gene promoter has an open chromatin conformation in the SW480 cell line, whereas the HeLa and Kb cell lines show a more compacted chromatin structure (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%